Effect of clamping distance and voltage on weldability of dissimilar welding - Veyolla, Jaffrey (2013)
In welding technology, there are a lot of parameters that would give different effects on the weldability, specifically in welding of dissimilar metal. In this study, carbon steel and stainless steel are welded by using metal inert gas welding or MIG by using ER308 filler wire and the parameters involve in this study are clamping distance and voltage. The objectives of this study are to study the effect of clamping distance and voltage on dissimilar welding and to determine which clamp is the most suitable in improving weld quality. The output for this study is focusing on the defects caused by different parameters and the hardness on the fusion zone. In this study, the current and speed is kept constant throughout the experiment. This study involves the microstructural preparation which involves the mounting, grinding, polishing, and finally the etching process in order to perform hardness test. Visual inspection is done by using naked eyes to determine the defects caused by different parameters. Comparison on the weld quality of sample welded by using same parameters including voltage is done to find out how different clamping distance would affect the weld quality. Parameter optimization is done by using Taguchi Method and Analysis of Variance is used to determine the most significant parameter that affects hardness at the fusion zone. From the analysis, the highest hardness value and minimum defects can be seen visually is on sample welded by using 21 V and 3.75 cm distance of clamping, which is by using clamp 2. The most significant parameter that affects the hardness is the distance of clamping. Confirmation test is done at the end to validate the result of experiment.